Epidemiology of mental disorders in Hernando Moncaleano-Perdomo University Hospital (2017-2018) - Alvis-Peña, Diego Julián (2021)
Introduction: Mental health is defined as a state of well-being in which the individual is aware of their own abilities, can face daily life activities, can work productively and can contribute to their community; but at the same time mental health is more than the absence of mental disorders, it is an integral part of health; So much so that there is no health without mental health. In Colombia, the Ministry of Health and Social Protection (MSPS), the five-year public health plan 2012-2021 (PDSP); Within the framework of Law 1751 of 2015, the Statutory Health Law, secondary to inequities in health services, the MSPS under Law 1751 builds the Comprehensive Health Care Policy (PAIS) and the comprehensive medical care model (MIAS) as the alternative for solving problems and for this, adopts strategies such as PHC with a family and community approach, comprehensive risk management and attention and a differential approach. Methods: Observational descriptive cross-sectional study with retrospective temporality of patients with mental disorders in a period between 2017 and 2018 in the municipality of Neiva Huila, at the Hernando Moncaleano Perdomo University Hospital (HUHMP). Results: depression was the most prevalent pathology with 24.16%, followed by schizophrenia with 14.62%. The average age was 36 years, the highest frequency was in the male gender with 55.32%, with a male-female ratio of 1.23. The service attended by the largest psychiatric population was through outpatient consultation with a percentage of 62.94%. Conclusions: Mental and behavioral disorders are a growing problem in mental health at a global, national and regional level, combined with the consumption of psychoactive substances since a dual pathology increases the risk of suffering from psychiatric pathologies. This internal characterization has allowed us to understand that the scandalous projections of Goldberg and Huxley are a reality, that are traced in the Department of Huila, and that our Mental Unit becomes a grain of sand in the desert.